Evaluative Aspect In The Semantics Of Phraseological Units With The Toponymal Component - Markova, Elena; Lyzlov, Alexei; Balkhimbekova, Perizat (Opción, 2019)
The purpose of this article is to study the axiological potential of phraseological units of the English language, one of the components of which is the toponymic element via the method of semantic analysis of the studied units. In result, in English linguistic culture people from northern counties are considered to be healthy tough simple-minded. In conclusion, evaluative potential of the studied units of the language is great, but the character of the described evaluative features is mostly different.